The Impact Of Village Funds On Enhanching Welfare Of North Maluku Communities Using Falah Approach - Batubara, Chuzaimah; Harahap, Isnaini; Marpuah, Siti (Universitas Islam Negeri Raden Intan Lampung, 2020)
The village fund is the government's effort to reduce poverty in villages in Indonesia, including in North Maluku. From the perspective of development funding, village funds play a major role in improving the quality of villages in North Maluku. But in fact, the poverty rate in North Maluku has actually increased. Based on these facts, this paper seeks to explain how the effectiveness of village funds is to reduce poverty and improve community welfare. To answer this problem, a qualitative research approach was carried out by the method of collecting in-depth interview data and focus group discussions with the village head, BPD and village communities.By conducting in-depth interviews and focus group discussions, this study found that village funds in Beringin Jaya and Akeguraci Villages in Tidore Kepulauan District and Ake Jailolo Village and Bobane Village, West Halmahera District, North Maluku, were able to improve the status of villages from disadvantaged to developing villages, but these changes are not followed by an increase in welfare (Falah). This is because village fund programs are more focused on infrastructure development but have not been able to meet economic and social aspects of life, such as providing life skills, enhancing harmony, and independence. The main problem is that human resources are still low both in terms of education level and quality of expertise so that village funds are managed as is.This study recommends that village funds are effective in reducing poverty, the village government needs to prepare a village development blueprint (renstra) in the next 5 years with clear indicators based on village achievements and the amount of village funds received. Village governments also need to send village fund managers to attend training on planning and reportingvillage financialKeywords: village funds, index, empowerment, Falah, North Maluku